2016
DOI: 10.1161/circep.116.004378
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Epicardial, Abdominal, and Overall Adiposity With Atrial Fibrillation

Abstract: Background-Although adiposity is increasingly recognized as a risk factor for atrial fibrillation (AF), the importance of epicardial fat compared with other adipose tissue depots remains uncertain. We sought to characterize and compare the associations of AF with epicardial fat and measures of abdominal and overall adiposity. Methods and Results-We conducted a meta-analysis of 63 observational studies including 352 275 individuals, comparing AF risk for 1-SD increases in epicardial fat, waist circumference, wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
123
0
10

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 169 publications
(137 citation statements)
references
References 81 publications
4
123
0
10
Order By: Relevance
“…1 Potentially distinct relationships between adipose subtypes and AF were highlighted in a recent meta-analysis of observational studies, which identified differential associations between overall, abdominal, and epicardial adipose and incident AF. 2 Further delineation of the association between adipose subtypes and AF risk could provide greater mechanistic and potential therapeutic insight into our understanding of AF pathogenesis.…”
mentioning
confidence: 99%
“…1 Potentially distinct relationships between adipose subtypes and AF were highlighted in a recent meta-analysis of observational studies, which identified differential associations between overall, abdominal, and epicardial adipose and incident AF. 2 Further delineation of the association between adipose subtypes and AF risk could provide greater mechanistic and potential therapeutic insight into our understanding of AF pathogenesis.…”
mentioning
confidence: 99%
“…Это предполагает самостоятельное значение эктопического висцерального жирового депо сердца как фактора риска развития ФП, подтверждением чему могут служить данные мета-анализа Wong C, et al [40]. Было показано, что увеличение на одно стандарт-ное отклонение объема ЭЖТ было ассоциировано с увеличением риска ФП в 2,6 раза (95% ДИ 1,89-3,6).…”
unclassified
“…Было показано, что увеличение на одно стандарт-ное отклонение объема ЭЖТ было ассоциировано с увеличением риска ФП в 2,6 раза (95% ДИ 1,89-3,6). Аналогичное изменение показателей ИМТ и окруж-ности талии сопровождалось увеличением риска арит-мии в 1,22 раза (95% ДИ 1,17-1,27) и в 1,32 раза (95% ДИ 1,25-1,41), соответ ственно [40].…”
unclassified
See 2 more Smart Citations